Impact of phosphoinositide-3-kinase and vitamin D3 nuclear receptor single-nucleotide polymorphisms on the outcome of malignant melanoma patients - Morgese, Francesca (Oncotarget, 2017)
BACKGROUND: Several studies associating single nucleotide polymorphisms (SNPs) frequencies with tumors outcome have been conducted, nevertheless malignant melanoma literature data are inconclusive. Therefore we evaluate the impact of different genotypes for phosphoinositide-3-kinase (PI3K) and vitamin D3 nuclear receptor (VDR) SNPs on melanoma patients’ outcome. MATERIALS AND METHODS: Genomic DNA of 88 patients was extracted from blood and tumor samples. SNPs were determined by PCR using TaqMan assays. We selected polymorphisms of the regulatory and catalytic subunit of PI3K (PIK3R1 and PIK3CA genes, respectively), analyzing rs2699887C>T of PIK3CA and rs3730089G>A of PIK3R1 SNPs. Furthermore we considered the following VDR SNPs: rs2228570A>G (Fok1), rs731236A>G (Taq1) and rs1544410C>T (Bsm1). Progression free survival (PFS) and overall survival (OS) were estimated with the Kaplan-Meier method and with Mantel-Haenszel log-rank test. RESULTS: The statistical analysis for Fok1 of VDR showed a significant difference in PFS after the first line therapy (median PFS= 21.2 months in the homozygous recessive genotype group vs. 3.3 months of homozygous dominant and heterozygous ones, p= 0.03). In particular, in homozygous recessive patients for Fok1 SNPs of VDR a high rate of histological regression and BRAF (B- Rapidly Accelerated Fibrosarcoma gene) mutation were observed. Furthermore, more efficacy of BRAF +/- MEK (MAPK-ERK-Kinase) inhibitors therapies in homozygous recessive patients vs. homozygous dominant and heterozygous ones was shown. CONCLUSIONS: Our study showed a significant correlation between homozygous recessive genotype of Fok1 SNPs of VDR gene and an increased PFS in patients who underwent a first line therapy with BRAF inhibitors.